Sulfated cellulose nanofiber and its dried product
Crosslinking sulfated cellulose nanofibers with chitosan or amines enhances the mechanical strength and water absorption of hydrogels, addressing their limitations in existing technologies and enabling applications in cosmetics and medical materials.
Patent Information
- Application Number
- JP2018198785
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2018-10-22
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2038-10-22
AI Technical Summary
Hydrogels, particularly those based on polysaccharides, suffer from poor mechanical strength, brittleness, and limited water absorption, which restricts their applications, especially in regenerative medicine and wound care, and they often lack biodegradability and biosafety.
A hydrogel is formed by crosslinking sulfated cellulose nanofibers with chitosan or amines, creating a three-dimensional network with enhanced mechanical strength and water absorption, and incorporating chitosan for antibacterial properties.
The resulting hydrogel exhibits improved mechanical strength, higher water absorption, and antibacterial activity, making it suitable for applications in cosmetics and medical materials.
Smart Images

Figure 0007626413000002 
Figure 0007626413000003 
Figure 0007626413000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a hydrogel derived from sulfated cellulose nanofibers (hereinafter sometimes abbreviated as "sulfate CNF." Furthermore, "cellulose nanofibers" may be abbreviated as "CNF."), a method for producing the same, and a dried product thereof. The hydrogel of the present invention can be suitably used for applications requiring moisturizing, water retention, antibacterial, antiviral properties, wound care, drug delivery, health care, etc. [Background technology]
[0002] Hydrogels are polymer matrices with a three-dimensional network structure in which hydrophilic polymer chains are physically or chemically crosslinked, and contain water, moisturizing agents, etc. The physical properties of hydrogels vary greatly depending on the number and positions of crosslinks. Applications of hydrogels include hygiene and cosmetics, wound care, artificial muscles, artificial cartilage, drug delivery, regenerative medicine, culture of organisms on a chip, agriculture and food, forensics and research, healthcare, etc. Polysaccharide-based hydrogels are particularly useful in many applications ranging from food, cosmetics, drug delivery, and tissue engineering.
[0003] However, the crucial weakness of hydrogels is their poor mechanical strength. In particular, general electrolyte gels are so fragile that they break easily just by touching them with a finger, making them completely unsuitable for applications that involve loads, greatly limiting the range of applications. In particular, for regenerative medicine, such as artificial muscles and cartilage, the gel strength issue must be resolved. Another issue for medical use is biosafety, and wound dressings are required to have antibacterial and antiviral activity as well as biodegradability. However, currently available superabsorbent polymer hydrogels are almost exclusively acrylic-based products and therefore are not biodegradable. In view of the increasing interest in environmental protection issues, there has been a great deal of interest in recent years in the development of superabsorbent materials based on biodegradable polymers that have properties similar to those of conventional superabsorbent polyacrylics.
[0004] Physical gelation of polysaccharides can be achieved by balancing solvophilic and solvophobic interactions. Reorganization of polymer chains can be achieved by solvent exchange, which is one of the processing methods to form simple hydrogel assemblies. Conventional techniques include chitosan hydrogel, cellulose nanofiber gel, CMC gel, HPC gel, and MC gel. However, the three-dimensional network structure of hydrogels derived from these cellulose derivatives is formed by physical action, so the hydrogels are weak. In addition, the water absorption rate is low.
[0005] For example, in 1990, Anbergen and Oppermann (Non-Patent Document 1) proposed a method for the synthesis of superabsorbent materials made entirely from cellulose derivatives. Specifically, they used hydroxyethyl cellulose (HEC) and carboxymethyl cellulose sodium salt (CMCNa), which were chemically cross-linked with divinyl sulfone in a basic solution. However, the absorption properties of such materials are not as high as those of acrylic-based superabsorbent materials.
[0006] Moreover, the acrylic acid-modified superabsorbent starch derivatives and cellulose derivatives described in Non-Patent Document 2 have high water absorption rates, but biological safety is taken into consideration.
[0007] In addition, Patent Document 1 discloses a cellulose sulfate gel obtained by adding a potassium salt or a sodium salt to water-soluble cellulose sulfate and heating and cooling it, which does not have a particularly high strength and elasticity, and also exhibits a water-synthetic phenomenon, making it insufficient for most applications. In order to improve these problems, Patent Document 1 also invents a method of generating a thermoreversible gel by adding a different water-soluble polymer to an aqueous solution of water-soluble cellulose sulfate and an alkali metal salt, but this requires the addition of a second water-soluble polymer, and the water retention rate (35 times or less) and strength of the resulting gel are low, and water syneresis occurs over time, causing a further decrease in water retention rate. In addition, since it is a thermoreversible gel, it returns to an aqueous solution when heated. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Japanese Patent Application Publication No. 57-206344 [Non-patent literature]
[0009] [Non-Patent Document 1] Anbergen U, Opperman W, Polymer, 31, 1854 (1990) [Non-Patent Document 2] Organic Synthesis Vol. 38, No. 6 (1980), pp. 546-554 Summary of the Invention [Problem to be solved by the invention]
[0010] The present invention aims to provide a sulfated CNF hydrogel by combining sulfated cellulose nanofibers with chitosan (B) or an amine (C). [Means for solving the problem]
[0011] The present inventors conducted extensive research to solve the above-mentioned problems and discovered that sulfated cellulose nanofibers (A), in which some or all of the hydroxyl groups on the surface have been modified by sulfate esterification, and chitosan (B) or an amine (C) can form a composite hydrogel, thereby completing the following invention.
[0012] [1] A hydrogel obtained by crosslinking sulfated cellulose nanofibers (A) in which some or all of the hydroxyl groups on the surface have been modified by sulfate esterification with a crosslinking agent, wherein the crosslinking agent is chitosan (B) and / or at least one amine (C) selected from the group consisting of diamines, triamines, and polyamines. [2] The sulfated cellulose nanofiber hydrogel according to [1], characterized in that the sulfated cellulose nanofiber has an average diameter of 1 to 20 nm, an average length of 0.5 to 10 μm, has a type I crystal structure, and is a sulfated cellulose nanofiber having 0.05 to 1.0 sulfate ester groups per anhydroglucan, which is a constituent unit of cellulose. [3] The sulfated cellulose nanofiber hydrogel according to [1] or [2], wherein the chitosan (B) is soluble in a solvent having an SP value of 10 or more. [4] The sulfated cellulose nanofiber hydrogel according to any one of [1] to [3] above, characterized in that when the crosslinking agent is chitosan (B), the weight ratio of the sulfated cellulose nanofiber (A) to the chitosan (B) is 98 / 2 to 40 / 60, and when the crosslinking agent is amine (C), the weight ratio of the sulfated cellulose nanofiber (A) to the amine (C) is 99.5 / 0.5 to 90 / 10. [5] A method for producing a sulfated cellulose nanofiber hydrogel, comprising mixing or contacting in a solution a dispersion (A') of sulfated cellulose nanofibers (A) or a salt thereof (A salt) in which some or all of the hydroxyl groups on the surface have been sulfated, with chitosan (B) or a solution (B') thereof, or at least one amine (C) selected from the group consisting of diamines, triamines, and polyamines or a solution (C') thereof. [6] A composite material obtained by drying the sulfated cellulose nanofiber hydrogel described in any one of [1] to [4] above. Effect of the Invention
[0013] The hydrogels using sulfated CNF as the starting sample have the following four characteristics compared to conventional polysaccharide hydrogels: (1) they have a high water absorption rate due to the sulfate esterification modification, (2) the three-dimensional network formed by ionic bonds between sulfate anions and the amino groups of chitosan (B) or amines (C) is strong, so the strength of the resulting hydrogel is significantly improved compared to carboxylic acid or hydroxyl groups. (3) Unlike cellulose derivatives such as carboxymethyl cellulose (CMC) and hydroxypropyl cellulose (HPC), the resulting hydrogels are stronger and more water-resistant because they are in the form of cellulose nanofibers. (4) The inventors have confirmed the biological activities of the sulfated CNF of the present invention, such as antiviral activity (e.g., phage, influenza virus, norovirus) and hyaluronidase inhibitory activity. Therefore, the hydrogels of the present invention can be expected to have similar biological activities.
[0014] In addition, compared with unmodified CNF or TEMPO-oxidized CNF, sulfated CNF has a higher water absorption rate or water retention rate of the sulfate ester group and has biological activity, making it promising for use in cosmetics, medical materials, etc.
[0015] Furthermore, by controlling the compounding ratio of sulfated CNF to chitosan or amine, the water absorption rate and physical properties can be controlled according to the application. [Brief description of the drawings]
[0016] [Figure 1] Image of sulfate CNF hydrogel [Diagram 2] IR spectrum of dried hydrogel [Diagram 3] Photographs of the hydrogels obtained in Examples 1 and 3 (left: Example 1; right: Example 3) DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The sulfated cellulose nanofiber hydrogel of the present invention has a three-dimensional network structure in which sulfated cellulose nanofibers (A) in which some or all of the surface hydroxyl groups have been modified by sulfate esterification are crosslinked with a crosslinking agent. The crosslinking agent is chitosan (B) or at least one amine (C) selected from the group consisting of diamines, triamines, and polyamines. It is preferable to use the chitosan (B) and the amine (C) as the crosslinking agent alone, but they can also be used in combination.
[0018] When sulfated cellulose nanofibers are crosslinked with a crosslinking agent, the sulfate ester groups form ionic bonds with the amino groups of the crosslinking agent to form a three-dimensional network. The crosslinking density can be controlled by adjusting the molar ratio of the sulfate ester groups on the surface of the sulfated CNF and the crosslinking agent.
[0019] Figure 1 shows an image of a hydrogel in which sulfated CNF is crosslinked with a crosslinking agent.
[0020] The types of crosslinking agents such as chitosan (B) and amine (C) are not particularly limited, but the structure of the crosslinking agent affects the crosslinking density, water absorption rate, safety, biological activity, etc. of the hydrogel, so they may be appropriately selected depending on the application. Among them, chitosan is particularly preferred because it is recognized to have antibacterial properties and biological activity, and is highly safe.
[0021] The sulfated cellulose nanofibers (sulfate CNF) used in the present invention are novel modified cellulose nanofibers that have not been known before. They have an average fiber diameter of 1 nm to 20 nm, a type I crystal structure specific to natural cellulose, and the hydroxyl groups on the surface of the cellulose nanofibers are modified by sulfate esterification.
[0022] The sulfated CNF used in the present invention has a type I crystal structure inherent to natural cellulose, and is therefore insoluble in water, and has high viscosity, thixotropy, and high mechanical strength. Furthermore, because this sulfated CNF has high hydrophilicity or water absorption, it can be easily redispersed even if it dries and becomes powdery, and is easy to handle. Therefore, hydrogels based on sulfated CNF are ideal for cosmetics, wound dressings, artificial cartilage, and the like.
[0023] On the other hand, natural sulfated polysaccharides, such as chondroitin, and artificially synthesized sulfated polysaccharides made from polysaccharides such as cellulose are also well known. However, these are not preferred because they do not have type I crystal structure, are soluble in water, are difficult to handle, and have low durability and mechanical strength.
[0024] There are no particular limitations on the sulfate modification rate of the surface hydroxyl groups of cellulose nanofibers (CNFs), but when the sulfur content of CNFs is used as a scale for evaluation, it should be 0.03% by weight to 35% by weight, and when the average degree of substitution is used as a scale, it should be 0.05 to 1.0 sulfate ester groups per anhydroglucan, which is a constituent unit of cellulose. More preferably, it is 0.1 to 0.8, and most preferably, it is 0.15 to 0.6. If it is 0.05 or less, it is not preferable because the water absorption is low and almost no biological activity can be found. On the other hand, if it is 1.0 or more, it is not preferable because there is a risk of losing the I-type crystal structure.
[0025] For CNF sulfate, the smaller the fiber diameter, the larger the surface area, which leads to higher water absorption, bioactivity, and transparency, making it preferable. However, if the average fiber diameter is less than 1 nm, it is not preferable because there is a risk of losing the I-type crystal structure. Also, if it is greater than 20 nm, it is not preferable because the surface area becomes small.
[0026] The longer the fiber length, the stronger the three-dimensional network, which is preferable. If the average fiber length is less than 0.5 μm, the obtained hydrogel will be weak, which is not preferable. The fiber length is preferably 0.5 to 10 μm, more preferably 0.8 to 8 μm. If the fiber length is too long, it will be difficult to handle, so the fiber length is most preferably 1.0 to 5 μm.
[0027] Sulfate CNF with type I crystal structure is preferred. The higher the ratio of type I crystal structure (degree of crystallinity), the stronger and more stable the resulting hydrogel will be, which is preferable. Sulfate CNF that does not have type I crystal structure is not preferable because it dissolves in water, which can lead to poor handling and a significant decrease in the physical properties of the resulting hydrogel.
[0028] The crystallinity of sulfate CNF prepared using cotton pulp or wood pulp as a raw material is practically difficult to exceed 90%, so it is preferably 20 to 90%, more preferably 30 to 85%, and most preferably 40 to 80%. Note that the crystallinity here is measured by XRD.
[0029] The sulfated CNF used in the present invention can be produced by the method described in WO2018 / 131721, a PCT application filed by the present inventor. The sulfate CNF used in the present invention has high water absorption and retention, thixotropy, viscosity, and mechanical properties, is biocompatible, and has been shown to have various biological activities, including antiviral properties, so it is expected to be useful as a medical material and cosmetic material.
[0030] The crosslinking agent used in the present invention is chitosan (B) or at least one amine (C) selected from the group consisting of diamines, triamines and polyamines.
[0031] The chitosan (B) used in the present invention is not particularly limited, but is preferably soluble in a solvent having an SP value of 10 or more.
[0032] Chitosan is obtained by deacetylating the acetamide group on the carbon at the 2-position in the chitin skeleton and converting it to a free primary amino group. Usually, the conversion of chitin to chitosan (deacetylation reaction) does not proceed completely, and in many cases N-acetylglucosamine is partially contained on the sugar chain. The higher the deacetylation rate or the ratio of amino groups, the higher the solubility of chitosan. If the deacetylation rate is too low, the solubility of chitosan will decrease, making it difficult to handle, and the crosslink density and antibacterial properties of the obtained hydrogel may decrease, which is not preferable. The deacetylation rate of chitosan used in the present invention is preferably 60% or more, more preferably 70%, and most preferably 80%.
[0033] The degree of polymerization of glucosamine constituting chitosan is not particularly limited. For example, 2 to 2000 is preferable. More preferably, it is 5 to 1500, and even more preferably, it is 6 to 1000. Most preferably, it is 6 to 500. When the degree of polymerization is 2 or more, the number of amino groups per molecule is two or more, so that a three-dimensional network can be formed. However, the lower the degree of polymerization, the lower the contact rate or reaction rate of the amino group of chitosan with the sulfate ester group of sulfated CNF, which is undesirable because the crosslinking density of the hydrogel decreases or free chitosan molecules may remain. On the other hand, if the degree of polymerization is too high, the solubility of chitosan may decrease, which is undesirable. From the viewpoint of solubility, the degree of polymerization is preferably 800 or less, and particularly preferably 500 or less. On the other hand, when the physiological activity of chitosan is required, a 6-mer to 15-mer having high physiological activity is most preferable. Therefore, a degree of polymerization of chitosan of 3 to 1000 is more preferable. Most preferable is chitosan having a degree of polymerization of 6 to 500.
[0034] Solvents that dissolve chitosan are more preferably those with an SP value of 11 or more. In particular, chitosan is preferably soluble in protic solvents such as DMAc, DMF, DMSO, methanol, ethanol, IPA, and water. The solubility of chitosan is affected by the molar ratio of its amino group to acetylamide group and the degree of polymerization of chitosan. The higher the ratio of amino groups, the higher the solubility, which is preferable.
[0035] The amine (C) used as the crosslinking agent in the present invention may be a diamine, triamine or polyamine, and is not particularly limited, but examples of the diamine include linear diamines such as ethylenediamine (2 carbons), putrescine (4 carbons), cadaverine (5 carbons) and hexamethylenediamine (6 carbons), or ethambutol and phenylenediamine, triamines include melamine and 1,2,3-propanetriamine, and polyamines include spermine and spermidine. Among these, triamines and polyamines are particularly preferred from the viewpoint of the strength of the hydrogel.
[0036] The ratio of sulfated CNF to crosslinker should basically be such that two or more amino groups per molecule of crosslinker react with the sulfate ester groups of the sulfated CNF to form a three-dimensional network, thereby forming a hydrogel. From the standpoint of the water absorption rate and biological activity (antiviral properties, etc.) of the hydrogel, the higher the ratio of CNF sulfate to crosslinker, the more preferable. On the other hand, from the standpoint of the antibacterial properties of the hydrogel, the higher the ratio of crosslinker, the more preferable. In order to prepare a hydrogel that has a good balance of these properties, it is sufficient to appropriately adjust the ratio of CNF sulfate to crosslinker. For example, when chitosan is used as the crosslinker, the weight ratio of CNF sulfate to crosslinker is I like The weight ratio of sulfated CNF to crosslinking agent is preferably 99.5 / 0.5 to 90 / 10, more preferably 99 / 1 to 92 / 8, and most preferably 98 / 2 to 95 / 5, since the amino group equivalent is small and the number of amino groups per molecule is small when the crosslinking agent is an amine.
[0037] If the amount of CNF sulfate or crosslinking agent falls outside the above weight ratio range and becomes excessive, gelation may not be possible or the gelation rate may be slowed down. In addition, the crosslink density of the resulting hydrogel may be low, which may result in a decrease in the strength and elasticity of the gel, which is undesirable. Moreover, if the crosslinking agent is used in excess, the proportion of unreacted amino groups remaining in the hydrogel increases, which in addition to the above problems also causes the problem of increased coloration of the gel.
[0038] When the proportion of crosslinker is higher than that of sulfated CNF and the molar ratio of sulfate ester groups to amino groups of the crosslinker exceeds 1, i.e., when the number of sulfate ester groups is greater than the number of amino groups, some of the sulfate ester groups of the sulfated CNF in the hydrogel will remain in the acid form (-SO3H). The sulfate ester groups of the sulfated CNF in the hydrogel may remain in the acid form (-SO3H), or the free sulfate ester groups may be changed to salt forms (-SO3M, where M is a monovalent cation). For example, the counter ions of some of the sulfate ester groups may be changed to alkali metal ions such as K+, Na+, and Li+, or ammonium ions (including organic ammonium ions; the same applies below), which is preferable because it increases the water absorption of the hydrogel. Furthermore, if sulfate ester groups remain, it is preferable to convert them into salts, since hydrogels having acid sulfate ester groups are prone to deterioration due to their acidity.
[0039] K + , Na + , Li + The higher the ratio of salt-type sulfate ester groups of alkali metal ions or ammonium ions, the softer the resulting hydrogel will be, and the higher its flexibility and water absorption. Conversely, the lower the ratio, the higher the crosslink density and strength of the resulting hydrogel will be. However, the water absorption rate will be lower. In other words, the ratio of salt-type and acid-type groups can be appropriately controlled depending on the application.
[0040] When the salt type is an organic ammonium ion, primary amines and secondary amines are more preferred from the viewpoint of basicity. Furthermore, from the viewpoint of hydrophilicity, the number of carbon atoms in the alkyl group of the amine is preferably 6 or less, and more preferably 4 or less. When an amine is used as a counter ion, the resulting hydrogel is stable against electrolytes. On the other hand, the higher the ratio of amine counter ions, the lower the hydrophilicity, which is not preferred. The sulfate ester group of the sulfated CNF is preferably 50% or less. More preferably, it is 40% or less, and even more preferably, it is 30% or less.
[0041] It is preferable that the sulfated CNF of the present invention further contains one or more of hyaluronic acid, collagen, glycerin, polyethylene glycol, and urea. By adding these components, the hydrogel can have the properties that each component possesses. In order to improve the moisture retention and biological activity of the hydrogel, it is preferable that the hydrogel contains at least one selected from the group consisting of hyaluronic acid, glycerin, polyethylene glycol, urea, and the like. Hyaluronic acid is most preferred as a wound dressing because it promotes maintenance of a moist wound site which promotes vascularization and wound healing.
[0042] The sulfate CNF of the present invention preferably further contains ceramic particles and / or hydroxyapatite particles. When the hydrogel is applied to regenerative medicine such as artificial cartilage, it is preferable that the hydrogel contains inorganic particles, which can improve the strength, hardness and durability of the hydrogel.
[0043] Next, the method for producing the CNF sulfate hydrogel of the present invention will be described. The sulfated CNF hydrogel of the present invention can be produced by mixing sulfated CNF (A) or a salt thereof (A salt) with chitosan (B) or at least one amine (C) selected from the group consisting of diamines, triamines, and polyamines in a solution, but it is preferable to use the sulfated CNF (A) or a salt thereof (A salt) as a dispersion.
[0044] A preferred method for producing a CNF sulfate hydrogel is to mix or contact in a solution a dispersion (A') of CNF sulfate (A) or a salt thereof (A salt) with chitosan (B) or a solution (B') thereof, or at least one amine (C) selected from the group consisting of diamines, triamines, and polyamines or a solution (C') thereof. It is more preferable to use the crosslinking agent in the form of a solution, since the quality of the resulting hydrogel, such as uniformity, is good, and the hydrogel can be controlled to have a desired shape.
[0045] In the present invention, there is no particular restriction as to whether a dispersion (A') of sulfate CNF (A) or its salt (A salt) is used. For example, after preparing sulfate CNF, sulfate CNF (A) obtained without neutralization has 100% of sulfate ester groups in the acid form (-SO3H). On the other hand, a salt of sulfate CNF (A salt) can be obtained by preparing sulfate CNF, and then converting some of the sulfate ester groups to the salt form (-SO3M) by partial neutralization, or converting all sulfate ester groups to the salt form (-SO3M) by complete neutralization.
[0046] Even if a salt of CNF sulfate (A salt) is used, when the salt of CNF sulfate is mixed with a crosslinker, the counter ion of the sulfate ester group is replaced by an amino group to form an amine sulfate salt. The original counter ion is converted, for example, to sodium hydroxide in the case of sodium, and is removed when the resulting hydrogel is washed.
[0047] The salt of the sulfated CNF (A salt) includes not only CNF in which all of the sulfate ester groups of the sulfated CNF form salts, but also CNF in which some of the sulfate ester groups are salts.
[0048] There is no particular limitation on the preparation of a dispersion of CNF sulfate or a salt thereof. For example, similar to the method described in WO2018 / 131721, a dispersion is obtained by dispersing CNF sulfate or a salt thereof in distilled water and stirring it with a mixer for several minutes. When CNF sulfate or a salt thereof is obtained as a dried powder, the powder can be dispersed in a dispersion medium such as water before use.
[0049] Examples of the dispersion liquid in which the sulfated CNF (A) or its salt (A salt) is dispersed include water, methanol, ethanol, cellosolves having an SP value of 11 or more, dimethyl sulfoxide, etc., which are capable of dissolving the crosslinking agent, and among these, water, ethanol, and dimethyl sulfoxide are preferred.
[0050] The concentration of the dispersion of CNF sulfate or its salt is not particularly limited, but is preferably 0.01 to 10% by weight. More preferably, it is 0.03 to 8% by weight, and even more preferably, it is 0.05 to 5% by weight. If the concentration is too low, it is not preferable because the gelation time may be long or the obtained hydrogel may be weak. On the other hand, if the concentration is too high, it is not preferable because the fluidity is low, making it difficult to control the shape of the hydrogel or air bubbles may be included in the hydrogel. Most preferably, it is 0.06 to 3% by weight.
[0051] If the viscosity of the dispersion of sulfated CNF or its salt is high, it may become dope-like. In the following, we will refer to this dispersion as a dope-like dispersion as well. When using a dispersion of CNF sulfate or its salt and the crosslinking agent itself, a CNF sulfate hydrogel can be produced by adding the crosslinking agent to the dispersion of CNF sulfate or its salt, and dissolving and mixing with stirring. The crosslinking reaction temperature may be room temperature to 70° C. The gelation time may be 10 to 60 minutes. The stirring method may be either mechanical stirring or a magnetic stirrer. The feature of this method is that the hydrogel can be easily produced, but the obtained hydrogel tends to be particulate.
[0052] When preparing a hydrogel using a dispersion of CNF sulfate or its salt and a solution of a crosslinker, there are a method of stirring and mixing both solutions and a method of contacting both solutions.
[0053] Examples of solvents for dissolving the crosslinking agent include, in the case of chitosan, water, acidic water, alcohols with an SP value of 11 or more, and dimethyl sulfoxide, among which water, methanol, ethanol, and dimethyl sulfoxide are preferred. In the case of amines, examples of solvents for dissolving the crosslinking agent include water, alcohols with an SP value of 11 or more, cellosolves with an SP value of 11 or more, and dimethyl sulfoxide, among which water, methanol, and ethanol are preferred.
[0054] The concentration of the crosslinking agent is not particularly limited, but if it is too low, the gelation speed may slow down or the crosslink density of the obtained hydrogel may be low, which is not preferable. On the other hand, if the concentration is too high, the crosslink density may become non-uniform or the crosslink density may become high, which is not preferable. The concentration is preferably 0.01 to 10% by weight. More preferably, it is 0.03 to 8% by weight, even more preferably, 0.05 to 6% by weight, and most preferably, 0.07 to 5% by weight.
[0055] The two solutions may be stirred and mixed under the conditions and by the method for mixing the dispersion of CNF sulfate or its salt with the crosslinking agent described above.
[0056] One method of contacting the two solutions is to add a solution of a crosslinker to a dispersion of CNF sulfate or its salt and leave it at room temperature to allow the crosslinker to penetrate the CNF sulfate dispersion and produce a CNF sulfate hydrogel. Alternatively, a dispersion of CNF sulfate or its salt can be injected from a nozzle into a solution of a crosslinker, and then allowed to stand at room temperature to produce a CNF sulfate hydrogel. In some cases, the CNF sulfate dispersion can be injected while stirring the crosslinker solution. Stirring has the effect of accelerating the penetration of the crosslinker into the CNF sulfate.
[0057] The gelation time is not particularly limited, and may be adjusted depending on the shape and size of the hydrogel and the desired crosslinking density, and is, for example, 0.1 to 24 hours, and more preferably 0.2 to 12 hours.
[0058] The temperature for forming the hydrogel or for the crosslinking reaction is not particularly limited, but is preferably 10 to 60°C, more preferably 15 to 50°C, and even more preferably 25 to 45°C. If the temperature is too low, the solubility of chitosan or amine decreases, and there is a risk of precipitation during gelation, which is not preferred. On the other hand, if the temperature is too high, there is a risk of the hydrogel being denatured, which is not preferred.
[0059] After a predetermined gelation time has elapsed, the resulting hydrogel can be further washed with distilled water to remove excess crosslinking agent and alkali consisting of counter ions of the sulfate ester groups substituted by the crosslinking agent.
[0060] Next, when the molar ratio of sulfate ester groups in the sulfated CNF hydrogel to amino groups in the crosslinker exceeds 1, sulfate ester groups will remain uncrosslinked. In this case, we will explain a method for converting the sulfate ester groups into salts.
[0061] To convert the sulfate ester group into a salt form, any of the following can be used. One method is to convert the acid-form sulfate ester groups into salts by immersing the resulting hydrogel having acid-form sulfate ester groups in a specific alkaline solution. In this case, the concentration of the alkaline solution is preferably 0.1 M or less, more preferably 0.05 M, and most preferably 0.01 M. If the concentration is too high, the bond between the amino group and the sulfate ester group formed by the crosslinking agent is broken, which is undesirable since it may cause a decrease in crosslink density or the gel to collapse. On the other hand, if the concentration of the alkaline solution is too low, the neutralization rate of the sulfate ester group or the conversion rate to a salt is too slow, which is undesirable.
[0062] Next, there is a production method in which a dispersion of a salt of CNF sulfate (A salt) is used from the beginning, and the molar ratio of the amino group in the crosslinking agent is made lower than that of the sulfate ester group salt of A salt. Since the crosslinking agent has few amino groups, unreacted sulfate ester group salts of the sulfated CNF remain.
[0063] In addition, when the dispersion of sulfated CNF (A) is mixed with the crosslinking agent, partial neutralization can be performed by simultaneously adding an alkali for neutralization.
[0064] In the present invention, in terms of the stability of sulfated CNF and the convenience of the hydrogel molding process, it is preferable to partially or completely neutralize the sulfated CNF after preparing it and before mixing it with the crosslinking agent.
[0065] By drying the hydrogel, a composite sheet of CNF sulfate and chitosan or amine is obtained, which can be used after absorbing the necessary solvent for application. Depending on the application, the nozzle can be selected to control the shape of the composite material. Examples include fiber, film, and sheet shapes. As a drying method, the hydrogel is dried within a temperature range of room temperature to 100°C to evaporate water. If the drying temperature is too high, the shape of the obtained composite material may collapse or crack, which is not preferable. A particularly preferable temperature range is 30 to 95°C, more preferably 40 to 90°C. Drying can be performed under normal pressure or reduced pressure. If the application requires denseness of the composite material after drying, drying at normal pressure and low temperature is preferable. On the other hand, if a porous composite material is required, drying at a higher temperature and reduced pressure is preferable. EXAMPLES
[0066] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples. The examples are examples of a hydrogel derived from sulfated CNF of the present invention and a method for producing the same.
[0067] [Production of CNF sulfate] Sulfate CNF can be produced in a manner similar to that described in the examples of WO2018 / 131721, but the production of sulfate CNF used in the present invention will be described below. Details of the materials and equipment used are as follows: (Cellulose, acetic anhydride, sulfuric acid and DMSO used) The raw cellulose used was cellulose pulp, which was a commercially available wood pulp (manufactured by Georgia Pacific, product name: fluff pulp ARC48000GP, moisture content: 9% by weight). Before defibration, the raw cellulose was cut into pieces small enough to fit into a sample bottle (approximately 1 cm to 3 cm square). Acetic anhydride, sulfuric acid and DMSO were purchased from Nacalai Tesque. (Stirrer) The stirrer used was a Mighty Stirrer (Model HE-20G) manufactured by Koike Precision Machinery Co., Ltd. A powerful oval stirrer was used. (mixer) To prepare the sulfated CNF, a Panasonic mixer (product number: MX-X701) was used.
[0068] (Manufacturing of CNF sulfate) 27 g of dimethyl sulfoxide (DMSO), 3 g of acetic anhydride, and 0.4 g of sulfuric acid were placed in a 50 ml sample bottle and stirred for approximately 1 minute using a magnetic stirrer at room temperature of 23°C to prepare a defibration solution. Next, 0.9 g of cellulose pulp was added and stirred at the same room temperature for an additional 120 minutes. After stirring, the reaction mixture was washed three times with 200 ml of distilled water to remove DMSO, acetic anhydride and residual sulfuric acid, yielding sulfated cellulose pulp. The resulting sulfated pulp (containing water) and 250 ml of distilled water were each placed in a mixer and stirred for five minutes to obtain an aqueous dispersion of sulfated cellulose nanofibers. The solid content was weighed to be 0.25 wt%. The average degree of substitution of sulfate ester groups was measured to be 0.35. FT-IR analysis (Figure 2) showed that the DMSO, acetic anhydride and residual sulfuric acid were removed from the reaction mixture at a frequency of 1250 cm -1 and 820cm -1 An absorption band characteristic of sulfate esters was detected nearby.
[0069] SEM observation revealed that the average fiber diameter of the sulfate CNF was 10 nm or less, and that it contained virtually no fibers with a diameter of 20 nm or more. In addition, the XRD pattern was similar to that of natural cellulose, confirming that it had a type I crystal structure. The degree of crystallinity was 60%.
[0070] The obtained sulfate CNF was evaluated as follows. (Observation of the shape of sulfated CNF) The shape of the sulfate CNF was observed using FE-SEM (manufactured by JEOL Ltd., product name: "JSM-6700F", measurement conditions: 20 mA, 60 seconds). The average fiber diameter was calculated by randomly selecting 50 fibers from the SEM image and averaging them. (Crystallization of sulfated CNF) The crystallinity of the obtained sulfate CNF was measured by XRD analysis (Segal method) based on the description in the reference (Textile Res. J. 29:786-794 (1959)) and calculated using the following formula. Crystallinity (%)=[(I200-IAM) / I200]×100% [In the formula, I200 is the diffraction intensity of the lattice plane (002 plane) (diffraction angle 2θ = 22.6°) in X-ray diffraction, and IAM is the diffraction intensity of the amorphous portion (the lowest part between the 002 plane and the 110 plane, diffraction angle 2θ = 18.5°)]. (Quantitative determination of average substitution degree of sulfate ester group of sulfated CNF) The sulfur content was quantified using the combustion absorption-IC method. That is, dried sulfate CNF (0.01g) was placed on a magnetic board and burned in an oxygen atmosphere (flow rate: 1.5L / min) in a ring furnace (1350℃), and the generated gas components were absorbed in 3% hydrogen peroxide solution (20ml). The obtained absorption liquid was made up to 100ml with pure water, and the sulfate ion concentration (wt%) was calculated from the ion chromatography measurement results of the diluted liquid. The average substitution degree was calculated from the sulfate ion concentration. For the analysis, an ion chromatograph ICS-1500 model manufactured by Thermo Fisher Scientific was used. The average substitution degree is the number of moles of sulfate ester groups per one glutan, which is a structural unit of cellulose. (IR spectrum) The dried sulfated CNF was analyzed by FT-IR (ATR mode) to confirm the sulfate esterification modification by the presence or absence of absorption bands at frequencies of 1250 cm-1 and 820 cm-1 derived from sulfate ester groups. The measurement was performed using a NICOLET MAGNA-IR760 Spectrometer manufactured by NICOLET in reflection mode. It was also used for the composition analysis of the dried hydrogel.
[0071] [Production of CNF sulfate hydrogel] (sulfuric acid CNF) The dispersion of sulfated CNF produced as described above was divided into two equal parts, and a specified amount of aqueous sodium hydroxide solution (concentration 0.4%) was added to each part to prepare two types of dispersion, one in which the sulfate ester groups were partially neutralized and the other in which they were completely neutralized. (Crosslinking agent used) The chitosan used was chitosan oligosaccharide manufactured by Tokyo Chemical Industry Co., Ltd. The molecular weight is 20,000, which is equivalent to a degree of polymerization of about 111. It is soluble in water. As the amine, hexamethylenediamine manufactured by Nacalai Tesque, Inc. was used.
[0072] (Preparation of an aqueous solution of crosslinking agent) As shown in Table 1, a chitosan solution was prepared by adding a predetermined amount of chitosan or hexamethylenediamine to a predetermined amount of distilled water and stirring with a stirrer.
[0073] (Preparation and Evaluation of Hydrogels) A 0.25% aqueous dispersion of CNF sulfate was added to a sample bottle, and the liquid surface was adjusted to be flat. Then, 10 g of the crosslinker solution was sucked up with a dropper and dripped along the wall of the sample bottle. The bottle was left to stand at room temperature for 24 hours, and the crosslinker was allowed to penetrate into the CNF sulfate dispersion and gelled. The gel was collected and washed several times with distilled water to remove excess crosslinker, resulting in a cylindrical hydrogel. The surface moisture of the hydrogel was wiped off with Kimwipe (trade name), and the weight was measured on a balance and evaluated as a measure of water absorption (weight of hydrogel / weight of CNF sulfate). The same hydrogel was left at room temperature for one week, and the weight was evaluated again, and the weight difference before and after leaving it was evaluated as a measure of water release.
[0074] (Evaluation of hydrogel strength) A 200 g weight was placed on the obtained cylindrical hydrogel (height about 2 cm, diameter about 2 cm), and after 30 seconds, the weight was removed to confirm whether the hydrogel returned to its original shape. If it returned to its original shape, it was evaluated as having good strength and elasticity, and if it did not return to its original shape or collapsed, it was evaluated as having poor strength or elasticity.
[0075] [Examples 1 to 4], [Comparative Examples 1 to 3] Based on the composition shown in Table 1, cylindrical hydrogels were prepared by the hydrogel preparation method described above with a gelation time of 24 hours, and then evaluated. The evaluation results are shown in Table 1. FIG. 3 shows photographs of the hydrogels obtained in Example 1) and Example 3 (left: Example 1; right: Example 3).
[0076] In both Examples 1 and 2, it was possible to produce hydrogels that were able to recover their shape after compression and had good strength and elasticity. Furthermore, in Example 1, which had a higher crosslinker concentration than Example 2, the water absorption rate of the resulting hydrogel was lower and the water separation rate ((weight after preparation−weight after standing) / weight after preparation) was higher. In addition, the hydrogel obtained in Comparative Example 1, which had a low concentration of the crosslinking agent, had a high water absorption rate, but it was found that the gel collapsed when a load was applied. Furthermore, in Comparative Examples 2 and 3, which did not contain a crosslinking agent, gelation did not occur, and no hydrogels were obtained. In Example 3, a cylindrical hydrogel was prepared in the same manner as in Example 1, except that 0.25 g of silica sol was added to the same amount of sulfate CNF dispersion as in Example 1. The particle size of the silica nanoparticles was 50 nm. The obtained hydrogel had a bluish-white color due to the silica nanoparticles. The evaluation results of the water absorption rate, water separation rate, and strength did not show any significant difference from Example 1. In Example 4, a hydrogel was prepared in the same manner as in Example 1, except that an amine was used instead of chitosan. The appearance was almost the same as in Example 1, but the water absorption rate and water retention rate were slightly lower than those in Example 1.
[0077] [Table 1]
[0078] Furthermore, the hydrogels obtained in Examples 1 to 4 and Comparative Example 1 were dried and analyzed by FT-IR. The results are shown in FIG. 2. In the case of the examples, -1 , 1650cm -1 , 1540cm -1 On the other hand, in Comparative Example 1, an absorption band at a frequency of 1730 cm -1 The absorption band was barely detectable, suggesting that chemical bonds were formed between the sulfate ester groups and the amino groups in the hydrogels prepared in Examples 1 to 4.
[0079] (Preparation and evaluation of dried hydrogels) A water dispersion of CNF sulfate of a given concentration was added to a transparent polystyrene rectangular case, and after the liquid surface was smoothed, the crosslinker solution was sucked up with a spotting stick and dripped along the peripheral wall of the case. The mixture was left to stand at room temperature for a given time to gel. The resulting gel was collected and washed several times with distilled water to remove excess crosslinker, yielding a sheet-like hydrogel. The sheet-like hydrogel was dried in a 50°C air drier for 5 hours, and then further dried at 90°C for 3 hours to obtain a dried sheet. The tensile strength of the resulting dried sheet was evaluated using a strength tester.
[0080] [Example 5] A sheet-like hydrogel was prepared and dried using the same amounts of sulfated CNF dispersion and crosslinker solution as in Example 1. The dried sheet had a thickness of 0.2 mm. Tensile properties were measured, and the sheet was found to be tough with strength and elastic modulus of 130 MPa and 3600 MPa, respectively. [Industrial Applicability]
[0081] Compared with unmodified CNF or TEMPO-oxidized CNF, sulfated CNF has a higher water absorption rate or water retention rate due to the sulfate ester group and has biological activity, which makes it promising for use in cosmetics, medical materials, etc.
Claims
1. A hydrogel obtained by crosslinking sulfated cellulose nanofibers (A) in which some or all of the hydroxyl groups on the surface have been modified by sulfate esterification with a crosslinking agent, the crosslinking agent being chitosan (B); The ratio of the sulfated cellulose nanofiber (A) to the crosslinking agent is 90 / 10 to 40 / 60 in terms of the weight ratio of the sulfated cellulose nanofiber (A) to the chitosan (B); A sulfated cellulose nanofiber hydrogel, characterized in that at least a portion of the sulfate ester groups form ionic bonds with the amino groups of a crosslinking agent.
2. The sulfated cellulose nanofiber hydrogel according to claim 1, characterized in that the sulfated cellulose nanofiber has an average diameter of 1 to 20 nm, an average length of 0.5 to 10 μm, an I-type crystal structure, and a sulfated cellulose nanofiber containing 0.05 to 1.0 sulfate ester groups per anhydroglucan, which is a constituent unit of cellulose.
3. The sulfated cellulose nanofiber hydrogel according to claim 1 or 2, characterized in that the chitosan (B) is soluble in a solvent having an SP value of 10 or more.
4. The method for producing a sulfated cellulose nanofiber hydrogel comprises mixing or contacting in a solution a dispersion (A') of sulfated cellulose nanofiber (A) or a salt thereof (A salt), in which some or all of the hydroxyl groups on the surface have been modified by sulfate esterification, with chitosan (B) or a solution (B') thereof; The ratio of the sulfated cellulose nanofiber (A) to chitosan is 90 / 10 to 40 / 60 by weight of the sulfated cellulose nanofiber (A) to chitosan (B); A method for producing a sulfated cellulose nanofiber hydrogel, characterized in that at least a portion of the sulfate ester groups form ionic bonds with the amino groups of the crosslinking agent.
5. A composite material obtained by drying the sulfated cellulose nanofiber hydrogel according to any one of claims 1 to 3.
Citation Information
Patent Citations
Composite antibacterial air filtration material and preparation method thereof
CN104524866A
Cellulose sulfate gel composition
JP1982206344A
Hydrophilic resin composition
JP2017082202A
Sulfuric acid esterification modified cellulose nanofibers and method for producing cellulose nanofibers
WO2018131721A1